Business strategy series (Bradford, United Kingdom : Emerald, 2007)
Business Strategy Series provides busy managers with a comprehensive series of executive briefings on a whole range of issues central to all cutting-edge corporate strategies. This journal brings together the strategic thought leaders behind many of the world's leading corporations including senior executives, top-flight consultants and business school gurus. So you get the expertise and insights of some of the world's leading authorities for a fraction of what it would cost to commission just one report.
Electronic access only.
Description based on : vol. 11, no. 1 (2010), title from Publisher's page, viewed May, 18 2013
Also available in print form
Keywords: Strategic planning -- Periodicals; Management -- Periodicals; Business planning -- Periodicals